The Impact of Loan Amount and Interest Rates on Micro MSME Sales Growth - Meylania SPS, Ni Made Ayu; Rebecca NS, Irene (Operations Research: International Conference Series, 2025)
Micro MSMEs are the backbone of the economy. This study analyzes the effect of the amount of bank loans on the sales growth of micro MSMEs. Using a simple linear regression analysis method, this study shows that an increase in the amount of loans significantly contributes to the sales growth of micro MSMEs. These results emphasize the importance of wider credit access for micro MSMEs to support their sales growth. This study also indicates that changes in interest rates do not have a significant effect on the sales growth of micro MSMEs. The policy implications of these findings are the need for more inclusive and affordable financing programs for micro MSMEs, as well as increasing their access to various alternative funding sources.